Shedding light on grey areas: examining the effect of technology-based collaboration on the learning outcomes of older and younger adults - Wolfson, Natalie E., author; Kraiger, Kurt, advisor; Beier, Margaret, committee member; Rhodes, Matthew, committee member; Diehl, Manfred, committee member (Colorado State University. Libraries, 2014)
Given the emergent aging workforce and the rapid rise of technology-based training tools in organizational settings, I designed two studies to gain greater insight into whether or not older learners require computer-based instructional designs that are different from younger adults. Specifically, I conducted two studies to examine the effect of technology-based collaboration on older and younger adults' learning outcomes. In Study 1, older and younger participants completed an online audiovisual training and reviewed training concepts either individually or in a chatroom context with other trainees. Results indicated that, across conditions, older adults performed worse on learning outcomes compared to younger adults and that older adults had a more negative perception of their chatroom experience compared to their younger counterparts. In Study 2, I strengthened the collaborative learning manipulation, re-assessed the relationship between online collaboration and learning across age groups, and investigated turn-taking as a method of facilitating performance during the chatroom discussion. The two main findings for Study 2 were the following: 1) Age and instructional design condition (individual vs. collaboration) interacted to predict transfer performance. Quite surprisingly, younger adults performed similarly in the individual and collaborative conditions while older adults improved their performance in the collaborative condition compared to the individual condition. In effect, collaboration eliminated the performance gap that existed between older and younger adults in the individual condition. 2) Within the collaboration groups, those who engaged in a turn-taking protocol did slightly worse in terms of recall performance compared to those in the free-for-all collaboration condition. These findings speak to the need for age-specific instructional design and suggest that turn-taking might not be a strategy for boosting learning in a chatroom setting.
Keywords: cognitive aging; technology-based training